Rituximab and its potential for the treatment of rheumatoid arthritis - Bryant, Adam (Dove Medical Press, 2006)
Rheumatoid arthritis (RA) is a chronic systemic inflammatory disorder which causes deforming joint disease and a spectrum of extraarticular manifestations. Poor disease control may lead to functional impairment and loss of independence. In recent times a prominent role for B cells in the pathogenesis of RA has been suggested. Two major theories have been postulated to explain the role of rheumatoid factor (RF) in the RA inflammatory process and the reason for RF overproduction; the loss of tolerance model and the autonomous mutated B cell model. With this in mind, strategies have been adopted to deplete B cells including the use of the anti-CD20 antibody rituximab. Rituximab leads to complement mediated lysis of B cells as well as antibody-dependant cellular cytotoxicity. It has been hypothesized that rituximab may also initiate apoptosis in RA and alter the ability of B cells to respond to antigen and other stimuli. Several recent studies using rituximab have demonstrated significant declines in RA activity providing evidence for the role of B cells in RA. Rituximab would appear to be a major addition to the increasing therapeutic options for sufferers of RA.